The Environment and Forestry Investigators’ Authority in Money Laundering Offenses - Muh. Afdal Yanuar (Faculty of Law, Universitas Lampung, 2021)
Investigators from the Ministry of Environment and Forestry (Kementerian Lingkungan Hidup dan Kehutanan/ KLHK) are not authorized to investigate the crime of money laundering in the elucidation of Article 74 of Law No. 8 of 2010, although they are authorized to investigate the crime of origin. However, the controversy over the interpretation of Article 74 of the Money Laundering Law was resolved by the Decision of the Constitutional Court Number 15/PUU-XIX/2021, which expands the meaning of 'predicate criminal investigator' in the provisions of Article 74 of the Money Laundering Law to become 'an official or agency authorized by legislation to carry out an investigation.' This paper attempts to describe the dynamics of the authority of KLHK investigators in investigating money laundering offences before and after the pronouncement of the Constitutional Court Decision Number 15/PUU-XIX/2021, including the matter of legal harmonization in the Money Laundering Law relating to the authority to investigate money laundering. This research is normative research with a conceptual approach, a statute approach, and a historical approach. Through this paper, this research can convey that before the Constitutional Court's Decision Number 15/PUU-XIX/2021, KLHK investigators were not authorized to investigate the crime of money laundering, and several legal disharmonies arose regarding the regulation of the authority to investigate money laundering. Meanwhile, after the Decision of the Constitutional Court Number 15/PUU-XIX/2021, all investigators authorized to investigate predicate crimes of money laundering offences, among other things, investigators of the Ministry of Environment and Forestry, are ex officio authorized to investigate money laundering offences. Furthermore, KLHK investigators are authorized to investigate money laundering offences against environmental and forestry crimes whose tempus delicti is before the pronouncement of the Constitutional Court Decision Number 15/PUU-XIX/2021.